Nondestructive Single-Atom-Thick Crystallographic Scanner via Sticky-Note-Like van der Waals Assembling–Disassembling - Moon, Ji Yun; Kim, Seung Il; Ghods, Soheil; Park, Seungil; Kim, Seunghan; Chang, Soo Hyun; Jang, Ho Chan; Choi, Jun Hui; Kim, Justin S.; Bae, Sang Hoon; Whang, Dongmok; Kim, Tae Hoon; et al. (Advanced Materials, 2024)
Crystallographic characteristics, including grain boundaries and crystallographic orientation of each grain, are crucial in defining the properties of two-dimensional materials (2DMs). To date, local microstructure analysis of 2DMs, which requires destructive and complex processes, is primarily used to identify unknown 2DM specimens, hindering the subsequent use of characterized samples. Here, a nondestructive large-area 2D crystallographic analytical method through sticky-note-like van der Waals (vdW) assembling–disassembling is presented. By the vdW assembling of veiled polycrystalline graphene (PCG) with a single-atom-thick single-crystalline graphene filter (SCG-filter), detailed crystallographic information of each grain in PCGs is visualized through a 2D Raman signal scan, which relies on the interlayer twist angle. The scanned PCGs are seamlessly separated from the SCG-filter using vdW disassembling, preserving their original condition. The remaining SCG-filter is then reused for additional crystallographic scans of other PCGs. It is believed that the methods can pave the way for advances in the crystallographic analysis of single-atom-thick materials, offering huge implications for the applications of 2DMs.
Keywords: Atomic spalling; Crystallographic; Crystallographic characteristics; Grain boundary orientation; Non destructive; Single-atoms; Single-crystalline; Sticky notes; Van der Waal; Van der waal heterostructure; atomic spalling; crystallographic; graphene; nondestructive; vdW heterostructure